Empowerment of Rural Communities Through Information Technology (IT) Training for Teenagers - Nurfitriani M. Siregar; Nurharisyah Hasibuan; Ali Syahbana; Kamaluddin, Kamaluddin; Mohd. Rafiq; Nurhidayah , Nurhidayah; Yanida Marbun; Khoiruddin Harahap (International Journal of Community Service Implementation, 2024)
Community Service Activities in utilizing IT for adolescents use simple media. The head of Bulu Mario Village provides opportunities for the community to enhance their knowledge and economy. IT training was chosen because it has several advantages, including the fact that the majority of adolescents have smartphones, making it easier for the community to market their products. The aim of the community service in Bulu Mario Village is to empower the community with Information Technology (IT) skills and abilities, helping them thrive in an increasingly IT-integrated modern era. Additionally, this program aims to build sustainable growth in Bulu Mario Village. The implementation of the community service uses the Participatory Action Research (PAR) method, which involves the participation of all stakeholders. The activities in this community service include data collection, counseling, training, and evaluation. The results of this service show that the program successfully increased literacy among the village community, especially adolescents. With IT, the community can engage in e-commerce, digital financial services, and various other online platforms, all of which contribute to inclusive economic growth, thereby making the community more prosperous. The impact of this program is that adolescents are able to boost their confidence in adopting and using IT to improve the quality of life in Bulu Mario Village, particularly for themselves, in creating opportunities for economic well-being